Biosynthesis of bioactive diterpenoids in the medicinal plant Vitex agnus‐castus. (14th February 2018) - Heskes, Allison M.; Sundram, Tamil C.M.; Boughton, Berin A.; Jensen, Niels B.; Hansen, Nikolaj L.; Crocoll, Christoph; Cozzi, Federico; Rasmussen, Simon; Hamberger, Britta; Hamberger, Björn; Staerk, Dan; Møller, Birger L.; et al.
Summary: Vitex agnus‐castus L. (Lamiaceae) is a medicinal plant historically used throughout the Mediterranean region to treat menstrual cycle disorders, and is still used today as a clinically effective treatment for premenstrual syndrome. The pharmaceutical activity of the plant extract is linked to its ability to lower prolactin levels. This feature has been attributed to the presence of dopaminergic diterpenoids that can bind to dopamine receptors in the pituitary gland. Phytochemical analyses of V. agnus‐castus show that it contains an enormous array of structurally related diterpenoids and, as such, holds potential as a rich source of new dopaminergic drugs. The present work investigated the localisation and biosynthesis of diterpenoids in V. agnus‐castus . With the assistance of matrix‐assisted laser desorption ionisation‐mass spectrometry imaging (MALDI‐MSI), diterpenoids were localised to trichomes on the surface of fruit and leaves. Analysis of a trichome‐specific transcriptome database, coupled with expression studies, identified seven candidate genes involved in diterpenoid biosynthesis: three class II diterpene synthases (diTPSs); three class I diTPSs; and a cytochrome P450 (CYP). Combinatorial assays of the diTPSs resulted in the formation of a range of different diterpenes that can account for several of the backbones of bioactive diterpenoids observed in V. agnus‐castus . The identified CYP, Vac CYP76BK1, was found to catalyse 16‐hydroxylation of the diol‐diterpene, peregrinol, to labd‐13 Z ‐ene‐9, 15, 16‐triol when expressed in Saccharomyces cerevisiae . Notably, this product is a potential intermediate in the biosynthetic pathway towards bioactive furan‐ and lactone‐containing diterpenoids that are present in this species. Significance Statement: Furan and lactone diterpenoids of the medicinal plant, Vitex agnus‐castus, have received interest for their potential as new dopaminergic drugs. Through the application of MADLI‐MS imaging, targeted transcriptomics and enzyme functional characterisation, we report the identification of six diterpene synthases and a cytochrome P450, that in different combinations, catalyse steps towards their biosynthesis.